O Litoral e a metrópole dinâmica imobiliária, turismo e expansão urbana na região metropolitana de Natal-RN - Silva, Alexsandro Ferreira Cardoso da (2010)
The metropolitan regions of Northeast Brazil are being gradually included in a scenario of international investments, which are motivated by the restructuring of both touristic and real-estate sectors. The new capital, real-estate developers and space configurations that result from this process indicate the need for the creation and implementation of public tools which should, at least, allow the mitigation of the urban impacts and environmental losses resulting from this situation. The effects on landscape and on the socio-spatial configuration result from the intensification caused by the dynamism of the "real estate-tourism" sector. There is a regional integration as an expression of the urban expansion of the metropolitan area of Natal. This study investigates the uniqueness of the restructuring and territorial integration of coastal areas and the strategies of the circuit of capital accumulation formed by linking the real estate to tourism. It is intended to increase the understanding about the strategies of tourism, real estate and public policy agents involved in this territorial reconfiguration and in the fund-raising needed for the investments, to understand the existing social and environmental effects and their future trends and also to understand the forms of spatial production as results from the practices of approaching the land transformation and the tourism valorization of the landscape, in a synchronous manner, first in the Northeast region and, as a focal study, in the Metropolitan Area of Natal. Likewise, it is intended to apprehend the current processes of metropolization of the eastern coast of Rio Grande do Norte, in addition to indicate its physical-territorial transformation and the types of projects/developments promoted by the market in the recent period. Based upon analysis undertaken for the Metropolitan Region of Natal RN, this piece of work presents some considerations on possible legal instruments that can be adjusted to the municipalities which are experiencing the impact of this peculiar and recent phenomenon in the region, caused by the arrival of the real estate-touristic capital. It is also intended to point out basic proposals to the forms of public intervention, in a speculative way, starting from a Metropolitan Planning project within a medium and long term